In-situ measurement of residential buildings with hempcrete walls: a case study - Memari, Ali M.; Mirzai, Nadia; Hashemi, Mahsa; Lu, Xinrui; Gracie-Griffin, Corey; Yi, Hojae; Lowe, Sarah Klinetob (Frontiers in Sustainability, 2025)
Given that over 95% of buildings are residential, there is an urgent need for carbon-storing materials and easy-to-construct methods to achieve energy-efficient and low-carbon homes, which can significantly impact CO2 reduction. Industrial hemp, used to produce hempcrete, is a promising construction material. Hempcrete, composed of hemp hurd and fibers mixed with lime and water, is currently used for thermal insulation and lightweight building blocks, intended for use in constructing non-load-bearing walls. With growing interest in hempcrete for home construction and a lack of comprehensive data on its performance, a case study assessed the thermal resistance of walls in a home retrofitted with hempcrete insulation in wood-framed walls. This paper focuses on practical in-situ instrumentation and determination of the thermal resistance of hempcrete walls in a retrofitted house. It also provides some basic background information on hemp and hempcrete. It discusses the practical application of the Heat Flow Meter Method for in-situ measurement of the thermal properties of hempcrete walls. The paper concludes with the developed thermal resistance of retrofitted hempcrete walls based on in-situ testing.